Model Bisnis Islamic Financial Technology Produk Bank Syariah di Kota Medan - Hariani MD, Pipit Putri; Rahmayati, Rahmayati; Mujiatun, Siti (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2020)
This study aims to provide a business model of financing processes in Islamic banks through the financial technology model. By outlining the process that is practiced at four Islamic banks, namely PT. Bank Muamalat, PT. BRISyariah, PT. Bank Aceh, and PT. North Sumatra Bank. So as to produce a model in the implementation of business financing products. This research method uses a qualitative descriptive approach through the stages of determining problems, interviews, and conclusions. Based on the financing procedures of the four Islamic banks, it was analyzed that PT. Bank Aceh and PT. Bank of North Sumatra still applies a manual system. PT. Bank Muamalat and PT. BRISyariah has implemented a combination of technology and manual processes, but PT. BRISyariah is more comprehensive than PT. Bank Muamalat. The results of the study prove that the fintech business model in the financing process at Islamic banks accelerates the financing process for customers.